2019
DOI: 10.3382/ps/pey603
|View full text |Cite
|
Sign up to set email alerts
|

Energy and protein dilution in broiler breeder pullet diets reduced offspring body weight and yield

Abstract: The objective of the current research was to evaluate transgenerational effects of maternal dietary energy and protein on growth, efficiency, and yield of broiler offspring. A factorial arrangement of treatments consisting of high and low ME and CP levels fed during the rearing and laying phases was used. The study was a final 2 × 2 × 2 × 2 factorial arrangement of treatments, including broiler sex. Ross 708 broiler breeder pullets (n = 933) were fed diets containing 2,736 (HE REAR ) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Moreover, proportional heart weight of males was greater than that of females. These results were expected because it is well established that females have a larger proportion of breast muscle ( Grey et al., 1982 ; Young et al., 2001 ; Moraes et al., 2014 , 2019 ; Zuidhof et al., 2014 ) and abdominal fat pad ( Brake et al., 1993 ; Moraes et al., 2014 ; Zuidhof et al., 2014 ; Humphreys, 2020 ) than males, whereas males have a greater proportional heart weight than females ( Brake et al., 1993 ; Zuidhof et al., 2014 ; Humphreys, 2020 ). In the restricted scope analysis, males had a greater proportional gut weight than females, which is consistent with van der Klein et al.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, proportional heart weight of males was greater than that of females. These results were expected because it is well established that females have a larger proportion of breast muscle ( Grey et al., 1982 ; Young et al., 2001 ; Moraes et al., 2014 , 2019 ; Zuidhof et al., 2014 ) and abdominal fat pad ( Brake et al., 1993 ; Moraes et al., 2014 ; Zuidhof et al., 2014 ; Humphreys, 2020 ) than males, whereas males have a greater proportional heart weight than females ( Brake et al., 1993 ; Zuidhof et al., 2014 ; Humphreys, 2020 ). In the restricted scope analysis, males had a greater proportional gut weight than females, which is consistent with van der Klein et al.…”
Section: Resultsmentioning
confidence: 78%
“…Male offspring have a greater final BW than females ( van der Klein et al., 2017 ; Humphreys, 2020 ). Moreover, females are documented to have a greater proportion of breast muscle ( Scheuermann et al., 2003 ; Zuidhof et al., 2014 ; van der Klein et al., 2017 ; Moraes et al., 2019 ) and fat pad ( Lippens et al., 2010 ; Zuidhof et al., 2014 ; van der Klein et al., 2017 ; Moraes et al., 2019 ; Humphreys, 2020 ) than males.…”
Section: Introductionmentioning
confidence: 99%
“…Protein undernutrition by partial albumen removal from the eggs during embryonic development diminished reproductive capacity of hens (Willems et al, 2016 ). Energy and protein dilution in pullet diets of broiler breeder may have detrimental effects on the performance of offspring (Moraes et al, 2019 ). Furthermore, progress of follicle development was attenuated although there were fewer developing follicles than the primordial follicles in malnutritional ewe fetuses (Lea et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, InfanteRodrيguez et al (2016) suggested that the increase in dietary protein in dry tropics enhanced growth performance and improved FCR of broiler chickens, which maintained BWG with lower feed intake. Another report suggested that reduced dietary protein in the broiler breeder pullets decreases offspring's body weight while moderate excess of dietary protein increases broiler meat yield (Bartov & Plavnik, 1998; Moraes, Pishnamazi, Wenger, Renema, & Zuidhof, 2019).…”
Section: Discussionmentioning
confidence: 99%